The Development of a Drought Warning System using Geo-information Technology, Nakhon Sawan Province - phengphit, narathip (Burapha Science Journal, 2024)
Background and Objectives : The research objective was to develop a warning system for monitoring drought using Geo-Information technology in Nakhon Sawan province based on multi-source satellite data Methodology : The study divides the factors used for analysis into three main groups. The first group consists of meteorological factors, including daily rainfall data from the Himawari-9 satellite, as well as air temperature and relative humidity data from the Aqua MODIS satellite. The second group includes biospheric factors, such as the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI) obtained from the Terra MODIS satellite. Both meteorological and biospheric factors are processed in real-time daily using Python script. The third group comprises physical factors of the area, including proximity to watercourses, soil drainage, slope, elevation, stream density, and sub-watershed size. All these factors are then used to analyze drought-prone areas. Furthermore, an automated drought risk area warning system was developed to provide geospatial information services through a website. The data is served by a Geo-server, and maps are displayed using OpenLayers, a JavaScript library. Main Results : The study found that Nakhon Sawan province has a moderate drought risk area covering 2,114,591 rai, or 35.05% of the total area, with the high drought risk area covering 1,810,103 rai, or 29.87%. Most of these areas are outside the irrigation zone, including Tak Fa District, Takhli District, Tha Tako District, Chum Tabong District, Lat Yao District, and Phaisali District. On the other hand, the low drought risk area, covering 918,031 rai, or 16.12% of the total area, is primarily found in Mae Wong, Chum Saeng, and Mae Poen districts. Conclusions : The warning system can display daily drought risk areas, rainfall, air temperature, relative humidity, NDVI, and NDWI via https://hss.nsru.ac.th/droughtNS/, providing essential information for decision-making and water management authorities.